PENGEMANGAN TES KEPRIBADIAN BERDASARKAN ORIENTASINYA - Hartini, Sri (Exsplorasi, 2009)
ABSTRACT Various test to measure personality have been widely developed by experts on psychometrics. The main objective of the study is to improve personality test developed by Erric Fromm Theory and Proof that what is recommended or not to test one’s personality base on orientation. Purposive Sampling Method was employed. The sample of this study was 50 students of the fifth semester of Law Facully of Slamet Riyadi University and haven obs. To collect the data, questionare with Likert Scale Technique was used. Then Factor Analysis Method was employed to analyze the data collected. The method is to extract factor tested. The results of this study: 1. Judgement of the test improved in therms of content of this test as same as the results of factor analysis. The two factors included (Being Mode and Having Mode) remain the same; 2. Varience of two factors is 30,570%. It means that the two factors have 30,570% contribution to personality construct - 18,143 (contributions of factor I. Being Mode) and 12,427% (contributions of factor 2, having Mode ) as seen in rotated Component Matrx ; 3. The instrument has higt realiability analysis scale. Thus the instrument improved is recommended to test one’s personality based on orientation. Keyword: personality-test and orientation